Analysis Factors Affecting Employee Performance of BKD East Java When Work from Home - Ayu Meirana (Airlangga Development Journal, 2022)
Covid-19 pandemic has had a tremendous impact on all aspects of people's lives around the world, including Indonesia. Therefore, the government issued a policy towards the civil servant work system to become Work from Home (WFH). Human resources in government agencies, especially in the Regional Civil Service Agency (BKD) of the East Java, are required to carry out their duties and obligations maximally so that performance increases, even though they do not work from the office. The sample of this research is 56 employees of BKD in East Java. The technique of collecting data through distributing questionnaires. The analysis tool used is Partial Least Square (PLS) analysis. This study concludes that the use of information technology has a significant effect on emotional intelligence, job stress, and employee performance. Emotional intelligence has a significant effect on employee performance. Meanwhile, job stress has no significant effect on employee performance.